Estrés académico en la formación online durante la pandemia del COVID-19 en estudiantes de la Facultad de la Salud Humana - Buele Banegas, Jamileth Stefania (2022)
In Ecuador, the prevalence of university academic stress is increasing, currently constituting 83%. The purpose of the study was to identify the sources of academic stress, evaluate the satisfaction of online training and relate both variables, according to sex and age in students of the Faculty of Human Health, period May-September 2020. Having a quantitative, descriptive approach, cross-sectional, with a probabilistic sample of 167 participants between 20-31 years of age; The Academic Stress Inventory and University Student Satisfaction Questionnaire were applied to online training. Obtaining that academic overload was the main source of stress in men aged 20-25 years and women aged 20-31 years; in men aged 26-31, it was future career prospects. The second source for both sexes of 20-25 years was the performance of an exam; in women aged 26-31 years it was the presentation of work and in men aged 26-31 years it was academic overload and lack of time to complete academic activities. In online training, the aspect with the greatest satisfaction in women aged 20-25 and men aged 20-31 were those related to the teacher-tutor; in women aged 26-31 years, it was the virtual environment. In contrast, the one with the least satisfaction in women between 20 and 31 years old and men between 20 and 25 years old were those related to the subject; in men aged 26-31 it was the virtual platform. Concluding that the female sex of 20-25 years presented a statistically significant relationship between the variables